2022
DOI: 10.21070/sej.v6i1.1620
|View full text |Cite
|
Sign up to set email alerts
|

The Effect Of Discovery Learning Models With Blended Learning Strategies Assisted By Crossword Puzzle Media On Understanding Physics Concepts

Abstract: This study aims to see the effect of the application of discovery learning models with blended learning strategies assisted by Crossword Puzzle media on the ability to understand students' physics concepts by choosing. This study used a pre-experimental method with a one-shot case study design consisting of 1 experimental class as a sample class which was carried out at SMP Negeri 1 Botupingge. The data obtained were in the form of understanding students' physics concepts on the material of vibration, waves, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 13 publications
(13 reference statements)
1
2
0
1
Order By: Relevance
“…Student enthusiasm in discussing the online assisted jigsaw model is a potential indirectly in mastering the concept of capita science II which discusses science learning at the junior high school level both in terms of science content (especially physics concepts combined with biology and chemistry concepts) and learning concepts and practices. The results of the research are in line with several learning studies that apply blended learning strategies to science concepts which affect learning outcomes both cognitively related to understanding concepts and problem solving skills (Odja & Hasan, 2022;Jelita et al, 2022;Bokingo & Odja, 2022)…”
Section: Resultssupporting
confidence: 82%
“…Student enthusiasm in discussing the online assisted jigsaw model is a potential indirectly in mastering the concept of capita science II which discusses science learning at the junior high school level both in terms of science content (especially physics concepts combined with biology and chemistry concepts) and learning concepts and practices. The results of the research are in line with several learning studies that apply blended learning strategies to science concepts which affect learning outcomes both cognitively related to understanding concepts and problem solving skills (Odja & Hasan, 2022;Jelita et al, 2022;Bokingo & Odja, 2022)…”
Section: Resultssupporting
confidence: 82%
“…By demonstrating Students' capacity to comprehend physics concepts is significantly impacted by the use of discovery learning models with blended learning techniques assisted by Crossword Puzzle media. According to the research's overall findings, which show that using physics concepts improves student learning outcomes (Bokingo et al, 2022;Raehan et al, 2020). The students reported that the crosswords covered the material they needed to learn in the session, that they had gained information that was relevant, and that they had a good understanding of the subjects they needed to study (Kalkan et al, 2022;Syofiani et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Physics is a branch of science that requires not only theories and formulas that need to be memorized but also understanding and comprehension of concepts that focus on knowledge formation through the discovery and presentation of data (Mahardika et al, 2012). Quality learning requires learning tools that can support students in understanding and mastering the material well (Bokingo et al, 2022;Gunada et al, 2017).…”
Section: Introductionmentioning
confidence: 99%